Rice Bran Oil Emulsion Organogels as Fat Baking for Brownies - Manakla, Sakunta; Jareonnon, Pattamaporn; Lilitchan, Supathra (Journal of Food Health and Bioenvironmental Science, 2023)
Rice bran oil emulsion organogels with different organogelators including triglyceride and policosanol are prepared and utilized as a bakery fat for making brownies. Texture profiles, percent of height gain, percent of weight loss, color, fatty acid composition, and sensory properties of the organogel brownies are investigated and compared with those of brownies made with rice bran oil and commercial margarine. The organogel brownies exhibit similar percent weight loss, percent height gain, hardness, gumminess and chewiness when compared to the commercial margarine brownies. Hardness, gumminess and chewiness in the organogel brownies are lower than rice bran oil brownie. The fatty acid compositions of both organogel brownies are similar to the rice bran oil brownie. Brownies prepared with the organogels exhibit considerable reduction in saturated fatty acid contents from 50.47% to 30.25% when compared with brownie prepared with commercial margarine. Policosanol and triglyceride organogels are potentially effective for producing nutritionally superior brownies with comparable quality attributes when compared to the margarine brownies.